Inhibitory effect of diethyl ether extract of the germinated brown rice in 3T3-LI adipocyte differentiation - Maruan, Ummi Hani (2016)
It has been disclosed that germinated brown rice have some pharmacological and biological characteristics. The aim of conducting this study is to probe the effect of diethyl ether extract of germinated brown rice on adipocytes. This study was conducted at Tissue Culture Laboratory, Universiti Teknologi Mara (UiTM) in Puncak Alam campus. This effects of diethyl ether extract of germinate brown rice were investigated by measuring viability of 3T3-L1 cells. The cells were treated with germinated brown rice extract at different concentration starting from 0, 62.5, 125, 250, 500 and 1000 µg/mL. The effect of diethyl ether extract of germinated brown rice on cell viability was determined by absorbance reading of MTS assay. It is found that at the concentration of 125 µg/mL, viability of 3T3-Ll cells significantly decreased (p < 0.001). The adipogenesis and changes in morphology of 3T3-L1 cells that were treated with germinated brown rice extract were measured by Oil Red-O staining assay. The result obtained show that accumulation oflipid droplet of 3T3-Ll cells ware significantly reduced (p < 0.05). Treatment with extracts of germinated brown rice decreased lipid accumulation. These results indicate that diethyl ether extract of germinated brown rice may be a beneficial tool for thwarting obesity through adipogenesis and lipid accumulation regulation.